The role of astrocytic γ-aminobutyric acid in the action of inhalational anesthetics - Won, Dongwook; Lee, Elliot H.; Chang, Jee-Eun; Nam, Min-Ho; Park, Ki Duk; Oh, Soo-Jin; Hwang, Jin-Young (Elsevier BV, 2024)
Background: Inhalational anesthetics target the inhibitory extrasynaptic gamma-aminobutyric acid type A (GABA(A)) receptors. Both neuronal and glial GABA mediate tonic inhibition of the extrasynaptic GABA(A) receptors. However, the role of glial GABA during inhalational anesthesia remains unclear. This study aimed to evaluate whether astrocytic GABA contributes to the action of different inhalational anesthetics. Methods: Gene knockout of monoamine oxidase B (MAOB) was used to reduce astrocytic GABA levels in mice. The hypnotic and immobilizing effects of isoflurane, sevoflurane, and desflurane were assessed by evaluating the loss of righting reflex (LORR) and tail-pinch withdrawal response (LTWR) in MAOB knockout and wild-type mice. Minimum alveolar concentration (MAC) for LORR, time to LORR, MAC for LTWR and time to LTWR of isoflurane, sevoflurane, and desflurane were assessed. Results: Time to LORR and time to LTWR with isoflurane were significantly longer in MAOB knockout mice than in wild-type mice (P < 0.001 and P = 0.032, respectively). Time to LORR with 0.8 MAC of sevoflurane was significantly longer in MAOB knockout mice than in wild-type mice (P < 0.001), but not with 1.0 MAC of sevoflurane (P=0.217). MAC for LTWR was significantly higher in MAOB knockout mice exposed to sevoflurane (P < 0.001). With desflurane, MAOB knockout mice had a significantly higher MAC for LORR (P = 0.003) and higher MAC for LTWR (P < 0.001) than wild-type mice. Conclusions: MAOB knockout mice showed reduced sensitivity to the hypnotic and immobilizing effects of isoflurane, sevoflurane, and desflurane. Behavioral tests revealed that the hypnotic and immobilizing effects of inhalational anesthetics would be mediated by astrocytic GABA.